Postoperative Bleed after PARS Plana Vitrectomy with Pre-Operative Intra Vitreal Bevacizumab in Diabetic Patients with Advance Diabetic Eye Disease - Muhammad Tahir, Tayyab Rehman, Muhammad Hamza Shahid, Muhammad Talha Farooq, M. Faisal Mitru, Sehrish Qayyum Khokhar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The aim of this study is to investigate the effect of preoperative intravitreal Bevacizumab on postoperative incidence of vitreous cavity hemorrhage in patients with advance diabetic eye disease undergoing 23 gauge pars plana vitrectomy. Study Duration: This study was conducted in the department of Ophthalmology Services Hospital Lahore from April 2021 to September 2021. Study Design: Randomized Controlled Trail Patients & Methods: Forty eyes of forty diabetic patients with advance diabetic eye disease were selected for three port 23 gauge pars plana vitrectomy (PPV) and were split into two groups of twenty patients each. One week before the pars plana vitrectomy, Group A received preoperative intravitreal bevacizumab (1.25 mg/0.05 ml) and sham injection were given to Group B patients and postoperative vitreous cavity bleeding was noted on day one , day three , day seven and bleeding was graded from no bleeding to mild and severe based on clinical examination. Practical implication: To assess the decrease in potential risk of postoperative vitreous cavity bleeding following 23 gauge three port pars plana vitrectomy Results: The patients in this study had an average age of 58.46 ±3.62 yrs and mean duration of diabetes among these patients selected for this trial was 11.25±1.52 years (range 8-22 years). Out of 20 eyes in Group A , 15 (75.0%) had no bleeding, 4 (20.0%) had mild and 1(5.0%) had severe postoperative vitreous cavity bleed. In group B , out of 20 eyes 11(55.0%) had no bleeding , 7(35%) had mild to moderate bleeding and 2(10.0%) had severe vitreous cavity hemorrhage. Conclusion: Preoperative Intravitreal bevacizumab prior to pars plana vitrectomy was found effective in reducing the risk of postoperative vitreous cavity bleeding in patients with advance diabetic eye disease. Keywords: Intravitreal Bevacizumab, advanced diabetic eye disease, vitreous hemorrhage, Postoperative bleed, Vitrectomy